2018
DOI: 10.1007/s12010-018-2803-6
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Diabetic and Anti-Nephritic Activities of Grifola frondosa Mycelium Polysaccharides in Diet-Streptozotocin-Induced Diabetic Rats Via Modulation on Oxidative Stress

Abstract: Grifola frondosa is an edible fungus with a variety of potential pharmacological activities. This study investigates the hypoglycemic, anti-diabetic nephritic, and antioxidant properties of G. frondosa polysaccharides in diet-streptozotocin-induced diabetic rats. After a 4-week treatment with 100 mg/kg of metformin and 200 mg/kg of one of four different G. frondosa polysaccharide mixtures (especially GFPS3 and GFPS4), diabetic rats had enhanced body weight and suppressed plasma glucose, indicating the hypoglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…In recent years, mushroom polysaccharides have been proven to have high antioxidant activity and assisted in the prevention of oxidative damage induced by ROS in living organisms [26]. Furthermore, previous literature had demonstrated that dysfunction of the brain and liver is closely related to aging and is susceptible to d-gal caused by oxidative injury [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, mushroom polysaccharides have been proven to have high antioxidant activity and assisted in the prevention of oxidative damage induced by ROS in living organisms [26]. Furthermore, previous literature had demonstrated that dysfunction of the brain and liver is closely related to aging and is susceptible to d-gal caused by oxidative injury [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, animal studies demonstrated that bioactive polysaccharide could inhibit the development of T2DM by decreasing oxidative stress. For instance, the polysaccharide obtained from Grifola frondosa (MW: 400–450 kDa) and Salvia miltiorrhiza Bunge (MW: 119.5 kDa) showed substantial defensive and antioxidative ability against the oxidative damage and increased the activities of antioxidant enzymes, such as SOD (superoxide dismutase), CAT (catalase), and GSH-Px (glutathione peroxidase) and decreased level of malondialdehyde (MDA), NO synthase, and inducible NOS (Nitric oxide synthase) in blood and liver [96,97]. MDA is measured as a fundamental chain reaction of lipid peroxidation, which produces injury to the cell membrane, necrosis, and inflammation [92].…”
Section: Mechanism Of Dietary Polysaccharides On Anti-diabetic Actmentioning
confidence: 99%
“…MDA is measured as a fundamental chain reaction of lipid peroxidation, which produces injury to the cell membrane, necrosis, and inflammation [92]. Additionally, G. frondosa and S. miltiorrhiza improved the insulin sensitivity index and attenuated STZ-induced structural changes to the pancreas and liver [96,97]. Similarly, the low molecular weight polysaccharides from Catathelasma ventricosum (MW: 160 kDa) and Ophiopogon japonica demonstrated anti-diabetic, anti-obesity, and antioxidant activities in STZ-induced diabetic mice.…”
Section: Mechanism Of Dietary Polysaccharides On Anti-diabetic Actmentioning
confidence: 99%
“…[ 10 , 11 ]. For example, antitumor polysaccharides from Ganoderma lucidum , three antioxidant polysaccharides obtained from Agaricus blazei Murrill, antidiabetic polysaccharides from Grifola frondosa Mycelium, four hypoglycemic polysaccharides from corn silk [ 10 , 11 , 12 , 13 ]. The extraction and application of polysaccharides is the interesting research point of the medicine and biology field.…”
Section: Introductionmentioning
confidence: 99%